(untitled) (Research, Society and Development, 2024)
Introduction: Chronic pain is a debilitating condition that affects millions of people globally, negatively impacting their quality of life. Defined as persistent pain for more than three months, it can result from various conditions such as arthritis, fibromyalgia, neuropathy, and chronic low back pain. Objective: This article provides a comprehensive overview of multimodal approaches in the treatment of chronic pain, reviewing pharmacological and non-pharmacological interventions and highlighting the importance of an integrated and holistic approach. Methodology: A literature review was conducted, identifying 23 relevant studies addressing pharmacological and non-pharmacological interventions in the treatment of chronic pain. The included studies varied in terms of design, studied population, and evaluated interventions. Results: Pharmacological interventions, such as analgesics, anti-inflammatories, opioids, anticonvulsants, and antidepressants, showed efficacy in relieving chronic pain. However, prolonged use of opioids was associated with significant risks of dependence and side effects. Non-pharmacological interventions, such as physiotherapy, acupuncture, and relaxation techniques, were effective in reducing pain and improving quality of life. Integrative approaches, combining pharmacological and non-pharmacological treatments, showed promising results. Discussion: The results highlight the importance of a multimodal approach in the treatment of chronic pain, combining pharmacological and non-pharmacological interventions to provide more comprehensive and effective care. Conclusion: Multimodal approaches are crucial for treating chronic pain, combining pharmacological and non-pharmacological treatments. Overcoming technological, privacy, and resistance challenges is essential for their success.